2020
DOI: 10.1108/jec-12-2019-0120
|View full text |Cite
|
Sign up to set email alerts
|

Handicaps and new opportunity businesses: what do we (not) know about disabled entrepreneurs?

Abstract: Purpose The process by which disabled individuals become entrepreneurs can be influenced by factors of different orders. Throughout their entrepreneurship careers and projects, disabled entrepreneurs may have to overcome multiple personal, social and political barriers. This study aims to review what we do (and do not) know about disabled entrepreneurs research to date. Design/methodology/approach The literature review focused on analyzing 42 articles from two databases, namely, Web of Science and Scopus. Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 78 publications
0
14
0
5
Order By: Relevance
“…Since our purpose is to encourage further research by applying a mainstream and influential perspective to a nascent field of disability entrepreneurship (see Kraus et al, 2020 for benefits of SLR in a nascent field), this article foregoes quantifying discrete elements such as word associations or frequency in the analysis. This work here should complement a recent systematic review by Mota et al (2020) who have taken a more comprehensive approach to describing the overall literature domain.…”
Section: Review Frameworkmentioning
confidence: 88%
See 3 more Smart Citations
“…Since our purpose is to encourage further research by applying a mainstream and influential perspective to a nascent field of disability entrepreneurship (see Kraus et al, 2020 for benefits of SLR in a nascent field), this article foregoes quantifying discrete elements such as word associations or frequency in the analysis. This work here should complement a recent systematic review by Mota et al (2020) who have taken a more comprehensive approach to describing the overall literature domain.…”
Section: Review Frameworkmentioning
confidence: 88%
“…Another 20 studies use quantitative surveys, and some contain a mix of PWDs/EWDs with non-disabled counterparts for comparison (Beisland et al, 2016;Mohammed & Jamil, 2015). Lastly, five articles are based on literature review, though there is only one SLR which is also the most recent (Mota et al, 2020).…”
Section: Descriptive Profile Of Selected Articlesmentioning
confidence: 99%
See 2 more Smart Citations
“…Another tool is the involvement of people with disabilities in business activities. Research by Mota et al (2020) confirmed that people with disabilities become self-employed entrepreneurs to avoid unemployment. For effective employment of disabled people there should be a comprehensive approach that includes a mechanism for interaction between different actors: employment services, educational institutions, public organizations, employers, medical and social expertise institutions (Arbuz, 2018).…”
Section: Problem Statementmentioning
confidence: 97%